Pengenalan Algoritma pada Pembelajaran Pemrograman Komputer - Hasan, Maulana; Yahfizham, Yahfizham (IAI Nasional Laa Roiba Bogor, 2024)
An algorithm is defined as a series of actions to solve a problem. The solutions implemented must be sequential, logical and systematic. In this way, algorithms can become the basis for creating computer programs. Meanwhile, a computer program is a set of commands that a computer is told to execute when solving a problem. Algorithms play a very important role in computer programming because the heart of computer science is algorithms. Many discussions from various branches of the computer field refer to the definition of algorithms. The purpose of this scientific work is to help students be able to first recognize the definition of an algorithm so that it can facilitate students' understanding of computer programming learning and increase student motivation in learning. The author used the literature study method in writing this scientific work. Keywords: Algorithms, Programming.